Identification and analysis of technology and knowledge transfer experiences for the agro-food sector in Mexico - Paula C. Isiordia-Lachica; Alejandro Valenzuela; Ricardo A. Rodríguez-Carvajal; Jesús Hernández-Ruiz; Jorge Alberto Romero-Hidalgo (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The purpose of this article is to contribute to the understanding of the effects generated by the technology and knowledge transfer processes in the agro-food sector, within the context of Mexico, a developing country where the economic sector is one of the most lagging in terms of technological development. To achieve this objective, academic-industry relations, key elements, results, and benefits will be examined in 87 identified cases. The analysis begins by describing the context of agriculture and the food industry in Mexico. Then, 14 cases are presented. Results show that companies implement new processes and methods or launch new products to the market, but also implement a new culture of innovation, by establishing laboratories and undertaking research areas of the firm, creating R&D programs which formalize and continue with the academy-industry alliances. The elements that were not found with the expected frequency, according to international scientific publications, was the participation of an available intellectual property.
Keywords: 650; agro-food; experiences analysis; knowledge transfer; technology transfer; university-industry collaborations